Proceedings of the Winter Simulation Conference 2014 2014
DOI: 10.1109/wsc.2014.7020009
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid agent-based and Discrete Event Simulation approach for sustainable strategic planning and simulation analytics

Abstract: Modern healthcare reforms are required to be financially, environmentally and socially sustainable in order to address the additional constraints of financial resources shrinkage, pressure to reduce the environmental impacts and demand for improving the quality of healthcare services. Decision makers face the challenge of balancing all three aspects when planning. However, implementing such an approach, particularly in healthcare, is not a trivial task. Modeling & simulation is a valuable tool for studying com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…We thus argue that a simulation approach chosen for TBL modeling may include both discrete and continuous modeling capabilities; this would address both short-term changes and the long-term evolution of the system under scrutiny. The argument is further strengthened by our experience of the combined use of two discrete approaches, ABS- DES 92 and SD-DES, 93 for sustainable planning in healthcare. The findings from the former showed that the application of the ABS-DES hybrid model for complex TBL-based systems could be tedious and, at some levels, prone to inconsistencies.…”
Section: Discussionmentioning
confidence: 99%
“…We thus argue that a simulation approach chosen for TBL modeling may include both discrete and continuous modeling capabilities; this would address both short-term changes and the long-term evolution of the system under scrutiny. The argument is further strengthened by our experience of the combined use of two discrete approaches, ABS- DES 92 and SD-DES, 93 for sustainable planning in healthcare. The findings from the former showed that the application of the ABS-DES hybrid model for complex TBL-based systems could be tedious and, at some levels, prone to inconsistencies.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, queue is a basic element in DES, which could model the efficiency and capacity of the system, but ABS does not contain this concept (Maidstone, 2012). Researchers have used ABS-DES hybrid model in analysing supply chain (Krejci, 2015;Mittal and Krejci, 2015), healthcare (Fakhimi et al, 2014 ;2015Liravias et al, 2015, transportation (Wang et al, 2014) and production (Barra Montevechi et al, 2015).…”
Section: )mentioning
confidence: 99%
“…Hybrid DES-ABM is described as the process from the entity's viewpoint, thus decentralize "some of" the rules. Goh, et al [37] describes the hybrid model in a simple manner as; the first component of the hybrid model is an ABM-DES model that analyzes a system in an individual level [39]. This component therefore produces data for the existing base case system, as well as, for systems to test strategic planning scenarios.…”
Section: Hybrid Des-abm Simulation Modellingmentioning
confidence: 99%
“…The second component is the intelligent DES workflow-based that takes as inputs the incident data that is generated from the base case and scenarios. The DES model then combines the timebased input data, and compares the KPIs between the simulated scenarios [39].…”
Section: Hybrid Des-abm Simulation Modellingmentioning
confidence: 99%